Math, asked by questioner9999, 4 months ago

Simplify (✓5-✓2)(✓2-✓3)​

Answers

Answered by karandangadhavi052
0

Step-by-step explanation:

-0.261 is the answer of this sum

Answered by Anonymous
12

 \mathtt\pink{SIMPLIFY}

 \mathtt{ =  (\sqrt{5}  -  \sqrt{2})( \sqrt{2}  -  \sqrt{3})  }

 \mathtt{ =  \sqrt{5}( \sqrt{2} -  \sqrt{3}) -  \sqrt{2}( \sqrt{2}   -  \sqrt{3}  )  }

 \mathtt{ =  \sqrt{10} -  \sqrt{15} -  { (\sqrt{2}) }^{2}   -  \sqrt{6}  }

 \mathtt{ =  \sqrt{10}  -  \sqrt{15}  - 2 -  \sqrt{6} }

Similar questions